Calibán y la bruja : mujeres, cuerpo y acumulación primitiva - Federici, Silvia (Abya-Yala : Instituto de Estudios Ecologistas del Tercer Mundo, 2016)
Moving from the peasant revolts of the late Middle Ages to witch hunts and the rise of mechanical philosophy, this book investigates the capitalist rationalization of social reproduction.